Work Life Balance and Organizational Commitment among Muslim Generation Y: The Effect of Islamic Work Ethic - Miranty Nurendra, Annisa; Puji Asmoko, Nuraini (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to explore the moderating effect of Islamic work ethic to work life balance and organizational commitment among generation Y. Methodology: Participants in this research were 166 Muslim employees, aged 24 to 39 years old. Data were collected using: 1) Work Life Balance Scale from Fisher, Bulger and Smith (2009), 2) Islamic Work Ethic Scale from Ali and Al-Owaihan (2008), 3) organizational commitment scale from Allen & Meyer (1990). Data were analyzed using structural equation modelling with SmartPLS 3.0. Results: Both of work life balance and Islamic work ethic have moderate correlation with organizational commitment. However Islamic work ethic has no moderating effect to the relationship between work life balance and organizational commitment. Applications: Practical implication of this study suggest organization should consider generation Y work life balance to maintain their commitment. It is also necessary to strengthening employee work ethic, especially in Islamic context.